The real and financial impact of COVID-19 around the world - Jens Klose; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2022)
In this paper, we study the impact of the COVID-19 pandemic in estimated panel VAR models for 92 countries. The large cross section of countries allows us to shed light on the heterogeneity of the responses of stock markets and NO2 emissions as high-frequency measures of economic activity. We quantify the effect of the number of infections and four dimensions of policy measures: (1) containment and closure, (2) movement restrictions, (3) economic support and (4) adjustments of health systems. Our main findings show that a surprise increase in the number of infections triggers a drop in our two measures of economic activity. Propping up economic support measures, in contrast, raises stock returns and emissions and, thus, contributes to the economic recovery. We also document vast differences in the responses across subsets of countries and between the first and the second wave of infections.
Keywords: E44; E52; E62; 330; COVID-19; lockdown-measures; panel VAR